Tax Literacy for SMEs in Lowokwaru Subdistrict to Improve Tax Compliance - Farras, Mohammad; Yuliati (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
This study contributes to small MSMEs in Lowokwaru District, whose tax compliance rates remain low. The objective is to examine tax knowledge and its impact on compliance among MSME operators. This study draws directly from informants experiences using qualitative phenomenological methods such as interviews, observation, and documentation. The results indicate that tax compliance among MSMEs remains low, including the use of e-Filing. MSMEs possess a moral awareness to comply, but exhibit low behavioral control, driven by fears of administrative errors and a lack of direct guidance. The novelty of this research lies in its phenomenological perspective, which reveals the subjective meanings held by MSMEs. This study demonstrates that trust in authorities and positive social experiences not merely formal legal threats significantly influence compliance. The study suggests shifting the tax authority’s approach from enforcement to service and guidance. Thus, to foster a culture of compliance among SMEs.